Prevalensi anemia pada ibu hamil di Puskesmas IV Denpasar Selatan Tahun 2015 - Yayang Christian; I Wayan Putu Sutirta Yasa (DiscoverSys Inc., 2019)
Introduction: The prevalence of pregnant women with anemia is quite high in Indonesia up to 63.5%. Though anemia can cause various complications in the fetus and in pregnant women themselves. There is still no data supporting the prevalence of anemia in pregnant women in Bali Province. The purpose of this study was to find the prevalence of anemia in pregnant women in Bali Province, especially the city of Denpasar and complete the data library regarding anemia in preganancy in Indonesia.Method: The research used cross-sectional design, and secondary data collection from medical record of Primary Health Care IV South Denpasar year 2015.Result: Anemia pregnant women amounted to 166 of total 521 pregnant women with 31.9% prevalence, with an average of 43 cases of pregnant women with anemia every month.Conclusion: From the data obtained found the prevalence of pregnant women who suffer from anemia is still relatively high (31.9%).